Structure‐function relationship of phenolic antioxidants in topical skin health products. (18th October 2016) - Jung, K.; Everson, R. J. C.; Joshi, B.; Bulsara, P. A.; Upasani, R.; Clarke, M. J.
Abstract: Objectives: The present work analysed the antioxidative activity of phenol‐based antioxidants using an electron spin resonance method to predict the activity and stability of these antioxidants in cosmetic products. Methods: The antioxidative power (AP) method was chosen to measure both the capacity and kinetics of an antioxidative reaction by detecting the DPPH (diphenylpicrylhydrazyl) radical. The antioxidative capacity ( w c ) relates to the amount of free radicals that can be reduced, whereas the antioxidative reactivity ( t r ) relates to the reaction speed and offers a fingerprinting of the redox state of the antioxidant molecules. Fifteen phenolic molecules have been analysed. They differed in the position of the hydroxyl groups and substituents on the aromatic ring. The AP of two distinct formulations containing hydroxytyrosol is presented as well as three phenol‐based antioxidants within the same formulation vehicle. Results: The rate at which phenol (ArOH) reacts with DPPH radicals, defined by the term reactivity ( t r ) in this paper, was dependent upon the bond dissociation enthalpy (BDE) of the OH bond. Molecules having weak OH bonds and consequently low BDE values showed high antioxidant reactivity. On the other hand, the capacity factor ( w c ), which is the concentration of phenol required to reduce a fixed concentration of DPPH radical, depends on the number and position of hydroxyl groups. The results showed that ortho and para positions of the two hydroxyl groups are important for higher capacity. If one of the two hydroxyl groups is blocked by methylation, both the antioxidative capacity and reactivity are reduced, mainly for ortho disubstituted compounds. The presence of a vinylic side chain improved reactivity and capacity tremendously. AP values may be useful in formulation design when identifying antioxidants that are likely to be physically and chemically stable. The importance of optimization of the formulation vehicle itself for a given antioxidant is also illustrated. Conclusion: Based on the presented findings, it is possible to predict the antioxidative performance of a phenol‐based molecule and its stability and oxidation resistance within a cosmetic formulation. This is essential for antioxidant containing dermal formulations designed to combat skin ageing. Abstract : The antioxidative activity of phenol‐based antioxidants was determined by using electron spin resonance. The method was used to predict the activity and stability of the phenolic antioxidants in cosmetic products. Based on the findings, it may be possible to predict the antioxidative performance of a phenol‐based molecule and its stability and oxidation‐resistance within a cosmetic formulation.